الاستثمار الاجنبي المباشر والمنظمة العالمية للتجارة: تحليل وتقييم اتفاقية اجراءات الاستثمار المتصلة بالتجارة على الدول النامية - حفاف, وليد (جامعة الوادي University of Eloued, 2016)
Abstract: Convention measures of investment trade-related are the first international convention, which put the rules for the treatment of foreign direct investment in the host countries, in the framework of the trading system of the GATT and the WTO Agreement. This agreement has a particularly important and It is treated the subject of the relationship between multinationals and host countries, As well as the potential effects of this convention on foreign direct investment and international trade pattern ,as well as its effects on economic development in developing countries. This paper seeks to study and analyze the provisions of this convention and to identify the potential effects on economies of developing countries, as well as the evaluation of this agreement by addressing the weaknesses and deficiencies, will also be discussion of the appropriateness of the World Trade Organization to address the issue of foreign direct investment. ملخص: يعد اتفاق اجراءات الاستثمار المتصلة بالتجارة بوصفه أول اتفاق دولي يقوم بوضع قواعد لمعاملة الاستثمارات الأجنبية المباشرة في الدول المضيفة في إطار النظام التجاري للجات ومنظمة التجارة العالمية، ونظرا للعلاقة الوثيقة بين الاستثمار الأجنبي المباشر والتجارة الدولية، يتمتع هذا الاتفاق بأهمية خاصة كونه يعالج موضوع العلاقة بين الشركات متعددة الجنسيات والدول المضيفة، وكذا الآثار المحتملة لهذا الاتفاق على الاستثمار الأجنبي المباشر وعلى نمط التجارة الدولية وكذا آثاره على التنمية الاقتصادية في البلدان النامية. سنسعى من خلال هذه الورقة البحثية إلى دراسة وتحليل أحكام هذا الاتفاق من أجل التعرف على الآثار المحتملة لهذا الاتفاق على اقتصاديات البلدان النامية، كما سنسعى إلى تقييم هذا الاتفاق من خلال التطرق إلى مواطن الضعف والنقص فيه، كما سنناقش مدى ملاءمة منظمة التجارة العالمية لتناول موضوع الاستثمار الأجنبي المباشر.
Foreign direct investment and the World Trade Organization analysis and evaluation convention measures of investment related to tread on developing countries P
مقال- مجلة رؤى اقتصادية
Keywords: الاستثمار الاجنبي المباشر، المنظمة العالمية للتجارة، اتفاقية اجراءات الاستثمار المتصلة بالتجار; Foreign Direct Investment, World Trade Organization, Agreement on Trade-Related Investment Measures (TRIMs)